2021
DOI: 10.1002/ejoc.202100659
|View full text |Cite
|
Sign up to set email alerts
|

3,10‐Diaryl Phenothiazines – One‐pot Synthesis and Conformational Tuning of Ground and Excited State Electronics

Abstract: A broad series of electronically diverse 3,10-diaryl phenothiazines was readily synthesized by a sequentially Pd-catalyzed three-component arylation-amination synthesis in a one-pot fashion in moderate to excellent yields. The diversity-oriented modular nature of the multicomponent reaction concept enables comprehensive investigations of electronic properties of the title compounds by absorption and emission spectroscopy, cyclic voltammetry, and quantum chemical calculations to elucidate their electronic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…This state is characterized by the absorption band between 400 and 520 nm which coincides with the absorption of the N , N ‐dimethylaniline cation. With the charge being localized on the substituent, the phenothiazine core is expected to change from a planar geometry, adapted by the radical species, to a bent geometry known for the neutral form [24b,39b–c] . This structural change is supported by DFT calculations (Figure S29) and will concomitantly change the angle between the phenyl ring and the phenothiazine core and reduce the electronic coupling between the two molecular fragments [37,41] .…”
Section: Resultsmentioning
confidence: 88%
“…This state is characterized by the absorption band between 400 and 520 nm which coincides with the absorption of the N , N ‐dimethylaniline cation. With the charge being localized on the substituent, the phenothiazine core is expected to change from a planar geometry, adapted by the radical species, to a bent geometry known for the neutral form [24b,39b–c] . This structural change is supported by DFT calculations (Figure S29) and will concomitantly change the angle between the phenyl ring and the phenothiazine core and reduce the electronic coupling between the two molecular fragments [37,41] .…”
Section: Resultsmentioning
confidence: 88%
“…In turn, the stronger overlap of the lone pair with the fused benzo moieties account for lower oxidation potentials. These electronic ground state effects can be further correlated in 3,10‐diaryl phenothiazines, which clearly show that enhanced electron donor character of phenothiazine can be best exploited when placing electron‐rich aryl donors on the nitrogen atom and electron‐withdrawing acceptors in the 3‐position, i. e., para to the nitrogen atom [11] …”
Section: Introductionmentioning
confidence: 91%
“…These electronic ground state effects can be further correlated in 3,10-diaryl phenothiazines, which clearly show that enhanced electron donor character of phenothiazine can be best exploited when placing electron-rich aryl donors on the nitrogen atom and electron-withdrawing acceptors in the 3-position, i. e., para to the nitrogen atom. [11] Since it was shown that N-acceptor substituted phenothiazines show an interesting, yet complex photophysical behavior and often dual emission, which can be attributed to the presence of intra-and extra-configurations of the chromophores, [8b,c,g] we propose, based on our experience with conformationally twisted triarylamine-TADF systems, [12] the design of N-anisyl phenothiazines bearing directly ligated or bridged terephthalonitrile acceptors in 3-position as configurationally uniform donor-acceptor systems that exploit the donor character of phenothiazine to a maximum extent. Herein, we report the synthesis, electronic properties and electronic structure of N-anisyl phenothiazine-terephthalonitrile donoracceptor dyads and acceptor-donor-acceptor triads.…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, 3,10-diaryl phenothiazines 104 were generated via a sequentially Pd-catalyzed three-component arylation-amination sequence in a one-pot fashion (Scheme 20A) (Mayer et al, 2020;Mayer and Müller, 2021). The consecutive Suzuki arylation-Buchwald-Hartwig amination sequence was applied to obtain 25 different examples of 3,10-diarylphenothiazines 104 in moderate to very good yields by varying arylboronic acids or esters as well as the aryl bromides with electron-donating and electron-withdrawing substituents in the para-position.…”
Section: Materials S30mentioning
confidence: 99%
“…Diacceptor substituted phenothiazine 107 can be accessed via a lithium formylation-Knoevenagel condensation (LiForK) sequence (May and Müller, 2020). The consecutive pseudo SCHEME 20 (A) Sequentially Pd-catalyzed arylation-amination consecutive three-component synthesis of 3,10-diaryl 10H-phenothiazines 104 (TRZ = 2,4diphenyl-1,3,5-triazine) (Mayer et al, 2020;Mayer and Müller, 2021). (B) One-pot sequence to synthesize disubstituted phenothiazine-triazine dyes 105 (Kloeters et al, 2022).…”
Section: Materials S30mentioning
confidence: 99%